Productivity in the Provision of Hospital Services: A Challenge to the Management Community - Longest, Beaufort B. (Academy of Management Review, 1977)
Productivity improvement has a role in holding down escalating costs of hospital services. A research model is developed for obtaining higher levels of productivity and quality in hospital departments. A challenge is issued to the management community for more research on hospital productivity.